The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1088/0953-2048/16/9/306
|View full text |Cite
|
Sign up to set email alerts
|

Local variations in the critical current degradation of Ag/Bi2223 tape by tensile and bending strains

Abstract: Using two types of tensile testing device, we have measured the strain dependence of Ic in AgMgNi-sheathed Bi-2223 57 core tapes at 77 K. The Ic degradation onset strains for the specimens with a short gauge length of 17.6 mm varied from 0.40 to 0.78%. In the relatively long samples with seven voltage terminals 5 mm apart along the gauge length of 60 mm, the smallest strain for the initiation of Ic degradation for the sections was 0.26%. The Ic in some other sections, however, began to degrade at larger strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 14 publications
3
43
0
Order By: Relevance
“…1-27 For description of damage behavior of Bi2223 filaments that transport superconducting current, two important parameters have been mentioned. 4,13,14,16,19,21,27 One is the intrinsic fracture strain Bi,f and another is the residual strain Bi,r . If the Bi2223 filaments are tested alone, they fracture at the intrinsic fracture strain Bi,f .…”
Section: Residual and Fracture Strains Of Bi2223 Filaments And Their mentioning
confidence: 99%
“…1-27 For description of damage behavior of Bi2223 filaments that transport superconducting current, two important parameters have been mentioned. 4,13,14,16,19,21,27 One is the intrinsic fracture strain Bi,f and another is the residual strain Bi,r . If the Bi2223 filaments are tested alone, they fracture at the intrinsic fracture strain Bi,f .…”
Section: Residual and Fracture Strains Of Bi2223 Filaments And Their mentioning
confidence: 99%
“…The mechanical properties are among the most important parameters for HTS tapes [1][2][3]. The relation of deformation and fracture behavior of multi-filamentary Bi2223/Ag composite tapes to the superconducting property has been studied widely [4][5][6][7][8][9]. It was revealed that the critical-current in the superconducting composite tapes under bending deformation decreases seriously beyond an irreversible strain, and once the applied strain exceeds such the irreversible strain, the critical-current never returns to the original value even when the applied strain is released [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The relation of deformation and fracture behavior of multi-filamentary Bi2223/Ag composite tapes to the superconducting property has been studied widely [4][5][6][7][8][9]. It was revealed that the critical-current in the superconducting composite tapes under bending deformation decreases seriously beyond an irreversible strain, and once the applied strain exceeds such the irreversible strain, the critical-current never returns to the original value even when the applied strain is released [4][5][6]. The influence of strain on the damage of superconductor filaments in Bi2223/Ag composite tapes was also observed in the experiment study by the scanning electron microscopy (SEM) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Heterogeneous damage occurs, and the damage evolution behavior differs from specimen to specimen and from location to location within a specimen. [9][10][11][12][13][14] Accordingly, when a number of specimens are tested, the critical current differs from specimen to specimen.…”
Section: Introductionmentioning
confidence: 99%